Social workers as expert witnesses. - National Association of Social Workers (Washington, DC : NASW Press, 2013)
"Social workers are frequently called to testify as experts in courts of law on a variety of subjects. Courts rely on information offered in evidence as the basis for decisions rendered, and oral testimony by witnesses is often the major source of evidence provided at a trial. Witnesses who testify as experts play a critical role in interpreting data, explaining complex material, and drawing informed inferences on the basis of their training and experience. Answering specific legal issues in particular jurisdictions often requires review of layers of applicable local, state, or federal laws that apply to a case. Although this law note is not intended to be a substitute for legal consultation regarding specific issues that affect social workers' expert testimony in a particular case, many examples are discussed, and social workers who do testify, or may be called to testify, as experts will want to have this volume ready to hand." -- Publisher website.
Introduction -- Who is an expert witness? -- Qualifying as an expert -- What can an expert witness testify to? -- What roles do social workers play as expert witnesses? -- How is a social worker retained to testify as an expert? -- Cases in which social workers qualify as experts -- Practical considerations -- Conclusion -- Endnotes -- Appendix A : federal rules of evidence -- Appendix B : sample letter of engagement -- Appendix C : annotated bibliography of cases -- Appendix D : Jaffee v. Redmond amicus brief.
Includes bibliographical references.
Keywords: Jaffee, Carrie -- Trials, litigation, etc; Evidence, Expert -- United States; Social workers -- Legal status, laws, etc. -- United States; Confidential communications -- Social case work -- United States